Pembuatan Desain Kemasan Menggunakan Aplikasi Corel Draw untuk Meningkatkan Minat Beli pada Setiawan Meat Kota Batu - Reyhan Hadani Setiawan; Heru Utomo; Dwi Sudjanarti (INDO PUBLISHING, 2026)
Setiawan Meat is a business specializing in selling of raw beef, operating with a commitment to providing high-quality products to consumers. One of Setiawan Meat’s innovative products is frozen food. This innovation aims to follow the ever-changing market trends and meet the customers need. Relate to that, the purpose of this study was to design packaging that can increase the customer buying interest in Setiawan Meat products. This study used the Action Research method, which consists of planning, action, observation, and reflection. The data collection methods included observation, interviews, and documentation. The unit of analysis included 1 owner, 2 marketing experts, 2 computer experts, and 10 consumers. The effectiveness of the design was measured with the EPIC model, which includes the dimensions of Empathy, Persuasion, Impact, and Communication. The purchase interest was measured with the AIDA model, which includes the stages of Attention, Interest, Desire, and Action. The results showed that in cycle 1, the packaging design was already in the